Assessment of skin temperature during regional anaesthesia—What the anaesthesiologist should know. Issue 9 (25th June 2018) - Hermanns, H.; Werdehausen, R.; Hollmann, M. W.; Stevens, M. F.
Abstract : Body temperature homeostasis is accurately regulated by complex feedback‐driven neuronal mechanisms, which involve a multitude of thermoregulatory pathways. Thus, core temperature is constantly maintained within a narrow range. As one of the most effective regulatory systems skin temperature is dependent on skin blood flow. Skin blood flow in turn is highly dependent on sympathetic activity. Regional anaesthesia leads to blockade not only of somatosensory and motor nerve fibres but also of sympathetic fibres. As a consequence, vasoconstrictor tonic activity is abrogated and a vasodilation leads to an increase in skin blood flow and temperature. The aim of this review was to summarize the general physiology of thermoregulation and skin temperature as well as the alterations during regional anaesthesia. The main focus was the usefulness of measuring skin temperature as an indicator of regional anaesthesia success. According to the available literature, assessment of skin temperature can indeed serve to predict success of regional anaesthesia. Hence, it is important to realize that relevant and reliable temperature increase is only seen in the most distal body parts, ie fingers and toes. More proximally, temperature changes are frequently small and inconsistent, which means that assessment of block levels is not possible by temperature measurement. Furthermore, relevant skin temperature increases will only be observed in patients, which are initially vasoconstricted. In conclusion, measurement of skin temperature represents a reliable and feasible diagnostic tool to assess and predict the success or failure of regional anaesthesia procedures, especially in patients in which sensory testing is impossible.